Characterization of synthesized (C6H5C2H4NH3)2PbCl4 perovskite crystals by a supersaturation evaporation method - Nguyễn Huy Tiệp (Journal of Military Science and Technology, 2022)
In this paper, we present research concerning the properties of single crystals (C6H5C2H4NH3)2PbCl4 (or PEAPbCl) synthesized by the supersaturation evaporation method at room temperature. The crystal structure, optical properties, transition temperature, and ferroelectric properties of the materials were investigated through X-ray diffraction (XRD), UV-Vis spectroscopy, photoluminescence (PL) spectroscopy, thermogravimetric analysis and differential scanning calorimetry (TGA - DSC), and ferroelectric hysteresis loop (P-E). The results show that PEAPbCl has a monoclinic crystal structure belonging to C 2/m space group dominated by (n00) signals, with n = 4, 6, 8, etc. a band gap of Eg ≈ 3.54 eV, and white light emission. The material has a transition temperature of TC ≈ 150 oC and a decomposed temperature of more than 200 oC. The ferroelectric hysteresis loop reveals the ferroelectricity of the material. This study offers an opportunity to use the potential PEAPbCl material in energy conversion and storage applications based on its interesting ferroelectric properties.